A comment on the equation of state for a degenerated gas - Gratton, Livio (1960)
In current literature on degenerated stellar configurations there seems to exist a strange misconception concerning the equations for relativistic degeneracv. As it is well known in a non-relativistic degenerated gas we can neglect the partial pressure of heavy particles due to the fact that in the equation of state for non-relativistic degeneracy the mass of the particles is contained in the denominator: with the usual notation.